Working Paper 42: From sanctions to confiscation while upholding the rule of law (Basel Institute on Governance Working Papers, 2022)
Written in the light of Russia's war of aggression in Ukraine, the Working Paper explores whether it is justifiable to confiscate assets frozen under financial sanctions in order to redirect them to the victims of state aggression. The paper first explores the concept of sanctions and financial sanctions (asset freezes) and what they mean in practice.Using the example of Canada, which has introduced a legislative mechanism for this purpose, the paper analyses whether states should be able to confiscate sanctioned assets purely on the basis that they have been sanctioned.It then looks at more established measures that states could adopt and apply to target sanctioned assets, including:• Traditional conviction based confiscation measures, including 'extended confiscation' mechanisms• Non-conviction based confiscation (forfeiture) measures• Unexplained wealth lawsThe paper recommends ways to maximise the effectiveness of these alternative avenues for recovering assets, which are much less controversial and can arguably be applied without infringing on legal rights. Opting for mechanisms that abide by established legal rights will not only significantly increase the chance of recovering assets without subsequent legal challenges. It will also ensure that the very reason for targeting the assets in the first place – namely to seek justice and compensation for acts of aggression – is not undermined through the erosion of the rule of law.
Keywords: sanctions; financial sanctions; asset freezes; non-conviction-based forfeiture; illicit enrichment; unexplained wealth; Russia; Ukraine